2019
DOI: 10.1002/ptr.6485
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanidin attenuates myocardial ischemia induced injury via inhibition of ROS‐JNK‐Bcl‐2 pathway: New mechanism of anthocyanidin action

Abstract: Despite treatment options available to date, myocardial ischemia (MI) remains the leading cause of death worldwide. Studies are focused on finding effective therapeutic strategies against MI injury. Growing interest has been developed in natural compounds possessing medicinal properties with scarcer side effects. Here, we have evaluated the cardioprotective potential of anthocyanidin against MI injury and explored its underlying protective mechanism. Left anterior descending coronary artery was ligated to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…If MI does occur, the oxidative stress reaction would be accelerated, thus, causing a large accumulation of oxygen free radicals, ROS production, and Ca 2+ overload, which would lead to aggravated myocardial injury and even cause cardiocyte apoptosis. 14 , 43 SOD, CAT, and GSH, as important antioxidant enzymes, can effectively eliminate oxygen free radicals and prevent ROS generation so as to protect myocardial tissue. In addition, excessive production of oxygen free radicals can cause lipid peroxidation and further myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If MI does occur, the oxidative stress reaction would be accelerated, thus, causing a large accumulation of oxygen free radicals, ROS production, and Ca 2+ overload, which would lead to aggravated myocardial injury and even cause cardiocyte apoptosis. 14 , 43 SOD, CAT, and GSH, as important antioxidant enzymes, can effectively eliminate oxygen free radicals and prevent ROS generation so as to protect myocardial tissue. In addition, excessive production of oxygen free radicals can cause lipid peroxidation and further myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been found that the stress‐activated JNK (p‐JNK) mediates phosphorylation of Bcl‐2 under ischemic conditions, which leads to irreversible cardiac injury. 14 Based on these studies, it appears that the level of ROS production and relative activity of MAPK pathway will determine whether cells survive or not. Therefore, this pathway may be a potential target for the therapy of MI disease by inhibition of oxidative stress and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be modulated also by exogenously administered cardioprotective compounds, including natural phenolic compounds [135,136]. As for the role of JNK/p38-MAPK in cardioprotective action of catechins, it has been documented that EGCG infused to the perfusion medium before regional I/R (35 min/2 h) in isolated rat hearts reversed I/Renhanced p38 phosphorylation and reduced IS [89].…”
Section: Jnk/p38-mapk Pathwaysmentioning
confidence: 99%
“…In myocardial I/R, the JNK pathway is activated mainly during the reperfusion period and was also reported to participate in ischemic preconditioning (for review see: [ 133 , 134 ]). It can be modulated also by exogenously administered cardioprotective compounds, including natural phenolic compounds [ 135 , 136 ]. As for the role of JNK/p38-MAPK in cardioprotective action of catechins, it has been documented that EGCG infused to the perfusion medium before regional I/R (35 min/2 h) in isolated rat hearts reversed I/R-enhanced p38 phosphorylation and reduced IS [ 89 ].…”
Section: Role Of Protein Kinase Pathways In Effects Of Catechins In Cardiac I/r Injurymentioning
confidence: 99%